Influenza infections in the 2014–2015 season and pregnancy outcomes - Ali Ozgur Ersoy; Serpil Unlu; Efser Oztas; Sibel Ozler; Dilek Uygur; Aykan Yucel (Journal of Infection in Developing Countries)
Introduction: The most recent influenza season saw a prominent infectious burden over a period of six months in the Turkish capital, reminding observers of the pandemic in 2009 year. The aim of the present study was to investigate the consequences of seasonal outbreaks in pregnant women during the 2014–2015 influenza season.